Implementasi Program Lembaga Dakwah Kampus untuk Meningkatkan Minat Mahasiswa Fakultas Dakwah - Risda Kurniawati; Wildan Yahya (UNISBA Press, 2023)
Abstract. This research is a study that discusses the Implementation of Campus Da'wah Institution Programs to Increase Interest of Da'wah Faculty Students. Al-Asy'ari Campus Da'wah Institution is a campus da'wah institution that plays a very significant role or has a very significant influence on campus da'wah, especially its role in facilitating structural members or non-members among students. In the realm of holding Islamic agendas as learning Islamic values. The purpose of this study was to find out the procedures for designing the Campus Da'wah Institution program for students, to find out the implementation of the Campus Da'wah Institution program for Unisba students, to determine the interest of Da'wah faculty students to the Campus Da'wah Institution program, to determine the inhibiting and supporting factors for the implementation of the Da'wah Institute program. Campus. The type of research used is qualitative research using qualitative descriptive methods. While the data collection techniques by means of observation, and interviews. The conclusions obtained from the results of this study are: In the procedure for designing the Campus Da'wah Institute program, there are two stages, namely work meetings, and work deliberation. Which in this design provides an overview of the program that is run by the organization, then the implementation of the program is carried out by setting up a committee and conceptualizing the process to be carried out so that it works properly, for the interest of the da'wah faculty students towards the Campus Da'wah Institution program, that the lack of student interest da'wah faculty against the Campus Da'wah Institute because it is caused by several things including, some students who participate in off-campus organizations or activities, there are also some students who carry out their studies while working, and then the inhibiting and supporting factors for the implementation of the Campus Da'wah Institute program, caused by problems communication from internal and external parties, the supporting factor is the support from other management members who are sensitive to the division's conditions that are not okay, there are also other supporting factors, namely the programs that can attract students. Abstrak. Penelitian ini merupakan penelitian yang membahas mengenai Implementasi Program Lembaga Dakwah Kampus Untuk Meningkatkan Minat Mahasiswa Fakultas Dakwah. LDK Al-Asy’ari merupakan Lembaga dakwah kampus yang berperan atau berpengaruh sangat signifikan dalam dakwah kampus khususnya berperan memfasilitasi para anggota atau non anggota secara kestrukturan dikalangan mahasiswa. Dalam ranahnya mengadakan agenda-agenda keislaman sebagai pembelajaran nilai-nilai Islam. Tujuan dari penelitian ini adalah,untuk mengetahui prosedur perancangan program LDK bagi mahasiswa, untuk mengetahui implementasi program LDK untuk mahasiswa unisba, untuk mengetahui minat mahasiswa fakultas dakwah terhadap program LDK, untuk mengetahui faktor penghambat dan pendukung implementasi program LDK. Jenis penelitian yang digunakan adalah penelitian kualitatif dengan menggunakan metode deskriptif kualitatif. Sedangkan teknik pengumpulan datanya dengan cara, observasi, dan wawancara. Kesimpulan yang diperoleh dari hasil penelitian ini adalah: Pada prosedur perancangan program LDK terdapat dua tahapan yaitu rapat kerja, dan musyawarah kerja. Yang mana dalam perancangan ini memberikan gambaran terhadap program yang kan di jalankan oleh organisasi, kemudian implementasi programnya dilakukan dengan cara menyusun kepanitiaan dan mengkonsep proses yang akan dilakukan agar bekerja dengan tepat, untuk minat mahasiswa fakultas dakwah terhadap program Ldk, bahwa minimnya minat mahasiswa fakultas dakwah terhadap Ldk karena disebabkan oleh beberapa hal diantaranya, sebagian mahasiswa yang mengikuti organisasi atau kegiatan di luar kampus, ada juga sebagian mahasiswa yang menjalankan kuliahnya sambil bekarja, dan kemudian faktor penghambat dan pendukung implementasi program Ldk, disebebkan karena adanya permasalahan komunikasi dari pihak internal dan eksternal, faktor pendukungnya yaitu terjadi dari dukungan anggota pengurus lain yang peka terhadap kondisi divisi yang tidak baik-baik saja, ada juga faktor pendukung yang lainnya yaitu program-programnya yang bisa menarik mahasiswa.